The Legal Advantages of Blockchain Technology For Notary Protocol Archives - Widya Kridawidyani; Ginting, Yuni Priskila; Fajar Sugianto (Faculty of Law, Mulawarman University, 2023)
The rapid progress of the development of information technology has made many changes in human life on this earth. Work and activities that used to be done manually are now shifting to using a technological approach. So far, notary services to the public are still conventional, but with the development of information technology, notary services inevitably must shift towards electronic services, which are currently known as cyber notaries. In Article 1 paragraph (13) of Law Number 30 of 2004 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary Public, it is explained that the Notary Protocol is one of the state archives, therefore the notary protocol must be treated like a state document kept and kept authentic. Therefore, the notary protocol must always be stored and maintained under any circumstances even if the notary who has the protocol is taking leave or has passed away. Because the Notary Protocol is categorized as a State Archive, the archive is also indirectly subject to Law Number 43 of 2009 concerning Archives. The Archives Act recognizes the existence of electronic archives. Blockchain technology offers a way to do digital archiving that is decentralized.